Synopsis of the genus Meridiotroctes Martins & Galileo (Coleoptera: Cerambycidae) - Machado, Vanessa S.; Monné, Marcela L. (Zootaxa, 2009)
Martins & Galileo (2007) proposed the genus Meridiotroctes to accommodate Meridiotroctes meridionale Martins & Galileo, 2007. They considered the new genus near Ozotroctes Bates, 1861 and to all the other genera recently described by Tavakilian & Néouze (2007): Formozotroctes, Psapharoctes, Punctozotroctes, and Spinozotroctes. All of these genera have in common the truncated apical segment of the labial palps (Tavakilian & Néouze, 2007: 20, figs. 21-33). Meridiotroctes meridionale, the only species of the genus, occurs in the states of Rio de Janeiro, São Paulo, and Santa Catarina, Brazil.